Value-added bioproducts or renewable energy derived from lignin? : comparative regional economic and environmental impact assessment : case Metsä Group's bioproduct mill in Äänekoski - Rannisto, Anna (2016)
Metsä Group’s next-generation bioproduct mill in Äänekoski will be operational within Q3/2017 and it will have significant regional economic impact on Central Finland. The mill will operate applying principles of circular economy, and thus utilize all possible side streams from pulp production. Lignin is one of the side streams that has huge potential to be refined, as sustainable products and by creating new value added. Conventionally, lignin is combusted with black liquor to generate energy in pulp mills. This thesis compares this conventional situation to refining lignin into biocomposite products made from 100% renewable resources with regard to regional economic and environmental impacts.